Reputation Repair After a Serious Restatement - Chakravarthy, Jivas; deHaan, Ed; Rajgopal, Shivaram (The Accounting Review, 2014)
ABSTRACT: How do firms repair their reputations after a serious accounting restatement? To answer this question, we review firms' press releases and identify 1,765 reputation-building actions taken by: (1) 94 restating firms in the periods before and after their restatement; and (2) a set of matched control firms during contemporaneous periods. We posit that firms have incentives to target multiple stakeholders in a reputation repair strategy—including capital providers, customers, employees, and geographic communities—and that actions targeting each group generate positive market returns as reputation capital is repaired. Consistent with our predictions, the frequency of, and stock returns to, reputation-building actions are greater for restating firms in the period after their restatement than for the control groups. In addition, firm characteristics predict the types of stakeholders targeted by firms. Finally, actions targeted at both capital providers and other stakeholders are associated with improvements in the restating firm's financial reporting credibility. Data Availability: The data used in this study are available from the sources indicated.